2015
DOI: 10.3109/0886022x.2015.1073528
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidin and fish oil potent activity against cisplatin-induced renal cell cycle arrest and apoptosis in rats

Abstract: Cisplatin is an effective chemotherapeutic agent that displays dose-limiting nephrotoxicity. In the present study, the efficacy of grape seed proanthocyanidin extract (GSPE: 100 mg/kg/day) and fish oil (FO: 5 mL/kg/day) against cisplatin-induced nephrotoxicity was evaluated in terms of DNA damage, histopathological changes and expression levels of molecular markers of apoptosis. The administration of cisplatin (CP) (7 mg/kg) results in an increasing percentage of S-phase, G2/M and apoptosis. Furthermore, CP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Caspases are mediators in the process of cell apoptosis. 66 They are proenzymes that control a cascade of proteolytic events ending in cell death. 67 Caspase-3 is particularly involved in the process of apoptosis by controlling Ca/Mg-dependent endonuclease which is involved in segmenting DNA ending in chromatin condensation and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Caspases are mediators in the process of cell apoptosis. 66 They are proenzymes that control a cascade of proteolytic events ending in cell death. 67 Caspase-3 is particularly involved in the process of apoptosis by controlling Ca/Mg-dependent endonuclease which is involved in segmenting DNA ending in chromatin condensation and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…That study showed that grape seed proanthocyanidins could prevent oxidative stress, genomic integrity, and cell death ( 49 ). The proanthocyanidins found in grape seed can prevent cisplatin-induced cytotoxic side effects in the kidney through modifying expression of the proteins associated with apoptosis and antioxidant property ( 50 ). Gao et al investigated the protective effects of grape seed proanthocyanidin extract on nephrotoxicity in male laboratory mice, and found that cotreatment with proanthocyanidins and cisplatin could result in decreased BUN level, renal index, and serum creatinine.…”
Section: Resultsmentioning
confidence: 99%
“…Lycopene: Carotenoids including lycopene are among the most potent antioxidants and prevent other oxidants from inducing toxic effects in the body. Hassan et al ( 50 ) reported that lycopene prevented cisplatin nephrotoxicity in mice through a complex process. Indeed, lycopene exerts its effects through reducing serum creatinine and BUN, preventing increase in MDA and isoprostane, decreasing renal bax protein as well as renal HSP60 and HSP70, increasing Bcl-2 expression, and decreasing lipids peroxidation ( 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…Flax and fish oil also showed normal kidney histology. Similarly, dietary flax and fish oil have shown to improve renal abnormalities in rats (Hassan et al 2015 ; Velasquez et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%